PENDAMPINGAN PEMBUATAN JAMU CELUP HERBAL PADA MASYARAKAT DUSUN DARUNGAN KECAMATAN SUKORAMBI - Susanti, Dhina Ayu; Nafista, Ulfia Fitriani; Danil, Muhammad; Hidayati, Sholihatil; Damiyanawati, Fatika Farah; Kalim, Karina (Universitas Mataram, 2025)
This community service activity is motivated by the local potential of Darungan Hamlet in utilizing herbal plants as health drinks, but is still limited in the aspects of processing, packaging, and marketing. This condition results in low product added value and limited economic opportunities for the community, especially members of the Catleya 3 Dasawisma Group. Motivating the mothers of the Catleya 3 Dasawisma members to become productive individuals will be an opportunity to improve and enhance the quality of family life economically. One effort that can be done is by providing scientific provisions that they can apply by creating something that has economic value. One of these is by making a health drink by utilizing natural resources that can grow well and are abundantly available in Jember. The goal of this activity is to increase the knowledge, skills, and economic independence of the community through innovative herbal dip products and the use of digital technology in marketing. The methods used include socialization, pre-tests and post-tests, training in making herbal dip with three flavors, application of production and packaging technology, and training in creating e-commerce-based marketing accounts. The target of the activity was members of the Catleya 3 Dasawisma Group located in the RT 04/RW 08 area of ​​Darungan Hamlet with a total of 20 participants. The increase in participants' understanding of the use of herbal medicines increased as seen from the average post-test score (80.53±15.80) which was higher than the pre-test score (59.47±13.93). Participants were able to produce herbal dip hygienically and of good quality, package products with attractive labels, and have knowledge related to product marketing through Shopee and Tokopedia. In addition, participants demonstrated independence in managing small businesses based on local potential with the support of production facilities and group communication. This activity succeeded in increasing community knowledge regarding the benefits of traditional medicinal ingredients and how to utilize them, entrepreneurial skills, and expanding participants' knowledge to create e-commerce accounts. Thus, the purpose of community service was achieved, namely the realization of increasing community skills in producing herbal dip sustainably.